Transcriptomic Analysis of Cadmium Stressed Tamarix hispida Revealed Novel Transcripts and the Importance of Abscisic Acid Network - Wang, Pei-Long; Lei, Xiao-Jin; Wang, Yuan-Yuan; Liu, Bai-chao; Wang, Dan-ni; Liu, Zhong-Yuan; Gao, Cai-Qiu (Frontiers in Plant Science, 2022)
Cadmium (Cd) pollution is widely detected in soil and has been recognized as a major environmental problem. Tamarix hispida is a woody halophyte, which can form natural forest on the desert and soil with 0.5% to 1% salt content, making it an ideal plant for the research on response to abiotic stresses. However, no systematic study has investigated the molecular mechanism of Cd tolerance in T. hispida. In the study, RNA-seq technique was applied to analyze the transcriptomic changes in T. hispida treated with 150 μmol L−1 CdCl2 for 24, 48 and 72 h compared with control. In total, 72764 unigenes exhibited similar sequences in the Nonredundant nucleic acid database (NR database), while 36.3% of all these unigenes may be new transcripts. In addition, 6778, 8282, and 8601 DEGs were detected at 24, 48 and 72 h, respectively. Functional annotation analysis indicated that many genes may be involved in Cd stress response, including ion bonding, signal transduction, stress sensing, hormone responses and ROS metabolism. A ThUGT gene from the abscisic acid (ABA) signaling pathway can enhance Cd resistance ability of T. hispida by regulating the production of ROS under Cd stress and inhibit absorption of Cd. The new transcriptome resources and data that we present in this study for T. hispida may facilitate investigation of molecular mechanisms governing Cd resistance.